Application of Technology in Mitigation of Forest and Peatland Fires in Riau Province to Support National Security - Syafrudin Fathoni; Nabella Nabella; Virana Fatwa Nurmala; M. Rizky Bayu Prayoga (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
The geographical, demographic, sociological, and historical location of Indonesia makes Indonesia's territory vulnerable to disasters. One of them is the province of Riau, which has a total area of ​​3,481,249 ha for forest and land fire disasters. Disaster management efforts must utilize science and technology optimally to simplify and speed up the disaster management process. For this reason, this research is aimed at knowing the role of technology such as weather modification technology, peatland water monitoring systems, and the Lancang Kuning application in dealing with the threat of forest and land fires. This research was conducted qualitatively with data collection techniques through interviews with the parties involved. The application of this technology has proven successful in keeping the sky in Riau Province blue. Of course, cooperation between various parties, whether civilian, military or the community, participates in the success of mitigation efforts in preventing the threat of forest and land fires in the province of Riau.